Cardiac Arrest (CA) as the Initial Presentation of Cocaine-induced Takotsubo Cardiomyopathy (TCM): Clinical Findings and Treatments - Catherina Almalouf; Narek Hakobyan; Vivek Yadav; Anjula Gandhi; Ruchi Yadav (Medicine and Medical Research: New Perspectives Vol. 7, 2024)
A unique case report of a 54-year-old male who developed Takotsubo cardiomyopathy (TCM) following recent cocaine use presenting with cardiac arrest (CA) has been presented. Cocaine is a sympathomimetic agent that acts by inhibiting the reuptake of norepinephrine, dopamine, and serotonin through binding with each transporter resulting in an accumulation of these neurotransmitters in the postsynaptic terminal. Cocaine is used as an illicit substance responsible for the most common cause of drug-related death. It is a stimulant that acts on the sympathetic nervous system and cardiovascular system leading to exaggerated, prolonged sympathetic activity due to the accumulation of neurotransmitters. Congestive heart failure, myocarditis, arrhythmias, and coronary artery spasms are among the cardiovascular adverse effects of cocaine. In the absence of obstructive coronary artery disease, takotsubo cardiomyopathy (TCM) is characterized by transitory akinesis, dyskinesis, or hypokinesis of the left ventricular (LV) wall with or without apical involvement. Cocaine-induced TCM is an extremely rare condition emphasizing the need for its prompt diagnosis by physicians. A case report of a 54-year-old male brought to the emergency department (ED) after an out-of-hospital cardiac arrest (CA), found to have TCM in the setting of cocaine use, has been presented. Clinicians need to understand the association between cocaine use and the development of TCM as cardiomyopathy of this type can result in complete remission after discontinuing the offending agent. There are no standardized recommendations for pharmacological treatment and prevention of episodes of TCM and further studies/trials need to be done to answer questions regarding the clinical diagnostic criteria, etiology, pathophysiology, and management of this syndrome. Categories: Cardiology, Internal Medicine, Substance Use and Addiction.